Association between Physiologic Parameters and Anatomic Location in Spontaneous Cerebrospinal Fluid Leaks. (2nd September 2014) - Shargorodsky, Josef; Xie, Yanjun; Solomon, David; Ishii, Masaru; Gallia, Gary; Reh, Douglas D.; Lane, Andrew P.
Abstract : Objectives: Although a relationship between elevated cerebrospinal fluid (CSF) pressure and spontaneous CSF leaks has been reported, analyses by anatomic sub‐site are lacking. This study seeks to elucidate the association between physiologic parameters and CSF leak location. Methods: Prospective case series of patients undergoing endoscopic endonasal repair of spontaneous CSF leak between 2004 and 2013. All participants had a lumbar drain placed for 24‐hour continuous preoperative pressure monitoring, and 24 hours of continuous monitoring starting 48 hours after the repair. In addition to patient characteristics, mean and peak CSF pressures by anatomic location were calculated and compared. Results: Twenty‐five patients underwent perioperative CSF pressure monitoring, with a mean follow‐up of 526 days. Nine patients had CSF leaks along the cribiform plate, 4 in the ethmoid roof, 8 in the sphenoid, 2 in the posterior table of the frontal sinus, and 2 with multiple leaks. Patients with cribiform leaks had the lowest mean body mass index (BMI) and prevalence of obstructive sleep apnea (22.2%), while those with multiple sites of leak had the highest mean BMI and prevalence of obstructive sleep apnea (50%). Patients with frontal sinus leaks had the highest postoperative mean (14.47 mmHg) and peak (42.5 mmHg) CSF pressures, while ethmoid roof had the lowest mean (0.43 mmHg) and peak (16.45 mmHg) CSF pressures. Conclusions: CSF pressure and other physiologic characteristics differ among patients with spontaneous CSF leaks by anatomic location. Understanding these differences may enable treatment approaches tailored by leak site, thereby improving repair outcomes.